Perancangan Sistem Informasi Akuntansi Penggajian (Manual) - Umi Kulsum; Moh Halim; Nina Martiana (COSTING : Journal of Economic, Business and Accounting, 2019)
Accounting information system is made to facilitate the execution of remuneration to be more efficient and effective, because this system is very influential for companies to meet the needs of external parties and management. This study was conducted to determine the payroll accounting applied by CV. Serampang Jaya. This type of research is a type of qualitative descriptive research with a case study approach that describes and explains a problem syteatically and factualy so that by gathering information relating to the object of resarch. The data sources used are primary data and secondary data. The data colection techniquesuse used are observation, interview, and docuentation. The technique used in analyzing is to develop and explain how the payroll accounting system applied by CV. Serampang Jaya. The use the design of employee payroll accounting information system on CV. Serampang Jaya is in acorndance with existing theories. The results showed that CV. Serampang Jaya has impleented a payroll accounting system but still needs improvements to be effective in the payroll accounting record process at CV. Serampang Jaya. Keywords: Payroll, Accounting, Information System